On the Stability of Money Demand in Ghana : A Bounds Testing Approach - Kovanen, Arto (IMF Working Papers; Working Paper, 2011)
This paper adopts the bounds testing procedure developed by Pesaran and others (2001) to test the stability of the long-run money demand for Ghana. The results provide strong evidence for the presence of a stable, well-identified long-run money demand during a period of substantial changes in the financial markets. The empirical evidence points to complex dynamics between money demand and its determinants while suggesting that deviations from the equilibrium are rather short-lived.1.